Effect of Intensive Blood Pressure Treatment on Heart Failure Events in the Systolic Blood Pressure Reduction Intervention Trial. (April 2017) - Upadhya, Bharathi; Rocco, Michael; Lewis, Cora E.; Oparil, Suzanne; Lovato, Laura C.; Cushman, William C.; Bates, Jeffrey T.; Bello, Natalie A.; Aurigemma, Gerard; Fine, Lawrence J.; Johnson, Karen C.; Rodriguez, Carlos J.; et al.
Abstract : Background—: Acute decompensated heart failure (ADHF) was a frequent common outcome in SPRINT (Systolic Blood Pressure Intervention Trial). We examined whether there was differential reduction in ADHF events from intensive blood pressure [BP] treatment among the 6 key, prespecified subgroups in SPRINT: age ≥75 years, prior cardiovascular disease, chronic kidney disease, women, black race, and 3 levels of baseline systolic BP (⩽132 versus >132 to <145 versus ≥145 mm Hg). Methods and Results—: ADHF was defined as hospitalization for ADHF, confirmed and formally adjudicated by a blinded events committee using standardized protocols. At 3.29 years follow-up, there were 103 ADHF events (2.2%) among 4683 standard arm participants and 65 ADHF events (1.4%) among 4678 intensive arm participants (Cox proportional hazards ratio, 0.63; 95% confidence interval, 0.46–0.85; P value =0.003). In multivariable analyses, including treatment arm, baseline covariates that were significant predictors for ADHF included chronic kidney disease, cardiovascular disease, age≥75 years, body mass index, and higher systolic BP. The beneficial effect of the intervention on incident ADHF was consistent across all prespecified subgroups. Participants who had incident ADHF had markedly increased risk of subsequent cardiovascular events, including a 27-fold increase ( P <0.001) in cardiovascular death. Conclusions—: Targeting a systolic BP<120 mm Hg, compared with <140 mm Hg, significantly reduced ADHF events, and the benefit was similar across all key, prespecified subgroups. Participants who developed ADHF had markedly increased risk for subsequent cardiovascular events and death, highlighting the importance of strategies aimed at prevention of ADHF, especially intensive BP reduction. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01206062